Sustainable reuse of dredged sediments as pavement materials by cement and fly ash stabilization - Yoobanpot, Naphol; Jamsawang, Pitthaya; Simarat, Peerapong; Jongpradist, Pornkasem; Likitlersuang, Suched (Journal of soils and sediments, 2020)
Purpose The process of removing sediments from the bottom of dams generates large amounts of dredged sediments, which are considered waste. The purpose of this research was to present the results of testing conducted on dredged sediment stabilized with ordinary Portland cement (OPC) and fly ash (FA) for reuse as pavement materials. Materials and methods The base sediment was high plasticity silt (MH) based on the Unified Soil Classification System (USCS). The experiments in this study consisted of unconfined compression (UC), California bearing ratio (CBR), and resilient modulus ( M r ) tests on stabilized dredged sediment. A combination of scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) was used to investigate the microstructures of the stabilized specimens. Finally, a simple comparative cost analysis between roads using conventional earthen materials and stabilized dredged sediment was performed. Results and discussion The results showed that the unconfined compressive strength ( q u ), CBR, and M r improved the pavement materials from unsuitable to suitable, and a 10% FA content provided the optimal strength enhancement. The SEM images showed that the calcium silicate hydrate (CSH) product, which was formed by hydration and pozzolanic reactions, attached to the clay clusters and filled the pore spaces between clay particles, resulting in a denser sediment structure. The EDX analyses showed that the calcium weight proportion and the silica-aluminum ratio were important factors in improving the strength of the dredged sediment treated with OPC and FA. These EDX results agreed with the q u , CBR, and M r results. For the studied situation, roads using stabilized sediment were 1.5 times more economical than roads using conventional earthen pavement materials. Conclusions Dredged sediments treated with OPC and FA can be sustainably reused as pavement materials based on the Department of Highways of Thailand standard, as well as the recommendations of Austroads ( 2017 ). Thus, for suitable sediments, reuse in road and pavement construction may be considered with appropriate treatment and conditioning.